The effect of a 10-week TOCA Football System intervention program on sport-specific motor skills among junior footballers - Szabó, Zoltán Tamás; Derkács, Evelin; Deli, Balázs; Prémusz, Viktória; Vass, Lívia; Pusztafalvi, Henriette; Ács, Pongrác (Frontiers in Sports and Active Living, 2024)
Introduction The objective of our study was to examine, in addition to using the TOCA Football System tool and training method, the effect of a 10-week intervention on elite youth athletes in terms of their sport-specific motor skills and anthropometric variables. Methods The study covered a group of 32 young players practicing football (U14) (13.45 ± 0.64 years). The junior U14 footballers were randomly assigned to an intervention or TOCA group (TG, N = 15, 13.25 ± 0.58 years) and a control group (CG, N = 17, 13.63 ± 0.66 years). Before starting the test, we performed full anthropometric measurements and assessed the sample's agility with and without the ball and their sport-specific endurance. The measurements were then repeated after the 10-week intervention. Results Within-group analysis showed significant improvements in muscle mass (p < 0.001), sport-specific endurance (p < 0.001), (p < 0.004) and agility (in TG) both with and without the ball (p = 0.002), (p = 0.004) however, we did not find a significant change in body fat percentage in either group (p = 0.988, p = 0.288). In the CG, “agility with the ball” changed significantly only (p = 0.023). In the between-group analysis with a repeated-measures analysis of variance (mixed-design ANOVA), there was no significant interaction in any performance variables. The main findings of this study indicate that a TOCA Football training program in addition to normal training during the in-season period does not produce additional effects in anthropometric factors, sport-specific endurance and agility performance with the ball (dribbling) and without the ball in comparison with the control condition. Discussion From a practical point of view, the presented anthropometric and physical profiles of players can be useful for football coaches in optimizing soccer training. Overall, it also can be concluded that the device can be safely used in the sensitive age group in terms of the development of motor skills since we did not find any negative effects during the use of the device in terms of the parameters we examined. In addition to the expansion of the number of elements and the inclusion of other age groups, it is advisable to carry out further complex tests, as the TOCA Football System offers many research opportunities.